Eleven quick tips for organizing a data cleaning challenge - Kal, Ireen J.; Smabers, Lidwien P.; von Berg, Joanna; Perticari, Giulia; van de Meent, Mette; Fokkelman, Denise; Sprangers, Joep; Lannelongue, Loïc; Dekkers, Florijn (PLOS Computational Biology, 2025)
null